Eyjafjallajökull satellite observations ... - Brodtkorb, André Rigland (Zenodo, 2020)
Satellite observations based on "Hourly non-gridded volcanic ash properties retrieved from SEVIRI measurements for the Eyjafjallajökull 2010 eruption" (Kylling and Sollum 2020, CC BY-SA 4.0, 10.5281/zenodo.3830363). The data has been regridded using fimex 1.4.2 to match the simulation domain MACC14 and thus be colocated with "Three-hourly gridded volcanic ash emissions for the Eyjafjallajökull 2010 eruption" (Brodtkorb et al., 2020, 10.5281/zenodo.3818196). These two datasets are used as input for the volcanic ash inversion routines in "metno/VolcanicAshInversion" (Brodtkorb, 2020, 10.5281/zenodo.3818001) ...